Embodied Placemaking: Filipina Migrant Domestic Workers’ Neighborhood in Beirut - Dalia Zein (Mashriq & Mahjar, 2021)
Based on a larger ethnographic project that investigates the spatial impact of the kafala (sponsorship) system on the access and mobility of migrant domestic workers (MDWs) in Beirut, Lebanon, this paper focuses on embodiment and the placemaking of Filipina MDWs in the city. From a theoretical lens that is placed at the intersection between the anthropology of space and place and feminist geography, I argue that the ways in which the precarious and marginalized community of Filipinas creatively makes place for themselves in the city despite spatial exclusion, labor restrictions, and employers’ control, ascribe new meanings to these already existing productions of Beiruti space. The argument is delivered through a spatial ethnographic analysis based on two months of participant observation and semi-structured interviews.